Physicochemical properties, cytotoxicity, and antioxidative activity of natural deep eutectic solvents containing organic acid - Mitar, Anamarija (Array, 2019)
Natural deep eutectic solvents (NADES) may be considered ‘designer solvents’ due to their numerous structural variations and the possibility of tailoring their physicochemical properties. Prior to their industrial application, characterization of NADES is essential, including determination of their physicochemical properties, cytotoxicity, and antioxidative activity. The most important physicochemical properties of eight prepared NADES (choline chloride:malic acid, proline:malic acid, choline chloride:proline:malic acid, betaine:malic acid, malic acid:glucose, malic acid:glucose:glycerol, choline chloride:citric acid, and betaine:citric acid) were measured as functions of temperature and water content. In general, the structure of prepared NADES greatly influences their physical properties, which could be successfully modified and adjusted by addition of water. All tested NADES were absolutely benign and noncorrosive for investigated steel X6CrNiTi18-10. Furthermore, cytotoxicity of prepared solvents was assessed toward three human cell lines (HEK-293T, HeLa, and MCF-7 cells), and antioxidative activity was measured by the Oxygen Radical Absorbance Capacity (ORAC) method. With regard to cell viability, all tested NADES containing carboxylic acid could be classified as practically harmless and considered environmentally safe. The ORAC values indicated that the tested NADES displayed antioxidative activity.